Nano-engineered edible films and coatings for seafood products - Koirala, Pankaj; Nirmal, Nilesh Prakash; Woraprayote, Weerapong; Visessanguan, Wonnop; Bhandari, Yash; Karim, Nurul Ulfah; Nor-Khaizura, Mahmud Ab Rashid; Saricaoğlu, Furkan Türker (Elsevier, 2023)
Seafood is a high-value market product well known for its nutrition and easily digestible protein. However, they are highly vulnerable to postharvest storage such as microbial deterioration and oxidation process (protein and lipid oxidation). Hence, various strategies have been employed to preserve the quality of seafood products, including chemical additives, natural preservatives, packaging, and coatings. This review discusses the recent advancement of nanotechnology in edible films and coatings for the shelf-life extension of seafood products. Firstly, quality changes in seafood products and biopolymers used in edible films and coatings have been summarized. A brief discussion has been provided on the various nanotechnology approaches to formulate nanoengineered edible films and coatings. Additionally, the quality and shelf-life extension of seafood products in terms of antioxidant and antimicrobial control using nano-engineered edible films and coatings have been discussed. Finally, safety, regulatory issues, and future prospectus on nano-engineered edible films and coatings are reported.